2020
DOI: 10.1186/s40468-020-00105-2
|View full text |Cite
|
Sign up to set email alerts
|

The application of Kunnan’s test fairness framework (TFF) on a reading comprehension test

Abstract: The present study tries to investigate the fairness of an English reading comprehension test employing Kunnan's (2004) test fairness framework (TFF) as the most comprehensive model available for test fairness. The participants of this study comprised 300 freshman students taking general English course chosen based on the availability sampling, three test developers, and seven university officials, administering the test. The main instrument is the teacher-made reading comprehension test to examine its validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Kunnan’s [ 27 ] TFF, prioritizing the role of test fairness, has broadened the span of fairness. The framework has been adopted in the research that investigates the fairness of large-scale assessments (e.g., [ 29 , 30 ]) and small-scale assessments (e.g., [ 10 , 12 ]). For large-scale assessments, Hamid et al [ 29 ] examined the fairness and justice of the IELTS and found a large proportion of participants believed that the test was not an accurate measure of their language abilities, and they were not satisfied with the IELTS justness in that they were not sure whether the test was a vehicle for increasing income or its suitableness for immigration purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kunnan’s [ 27 ] TFF, prioritizing the role of test fairness, has broadened the span of fairness. The framework has been adopted in the research that investigates the fairness of large-scale assessments (e.g., [ 29 , 30 ]) and small-scale assessments (e.g., [ 10 , 12 ]). For large-scale assessments, Hamid et al [ 29 ] examined the fairness and justice of the IELTS and found a large proportion of participants believed that the test was not an accurate measure of their language abilities, and they were not satisfied with the IELTS justness in that they were not sure whether the test was a vehicle for increasing income or its suitableness for immigration purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For large-scale assessments, Hamid et al [ 29 ] examined the fairness and justice of the IELTS and found a large proportion of participants believed that the test was not an accurate measure of their language abilities, and they were not satisfied with the IELTS justness in that they were not sure whether the test was a vehicle for increasing income or its suitableness for immigration purposes. Moghadam and Nasirzadeh [ 30 ] investigated the fairness of a locally developed English proficiency test and found that the test was acceptably fair from the perspectives of access, administration, and social consequences. But the validity of the test should be enhanced; and one item was flagged as gender DIF which needed further revision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clearly, the consequential matters of test fairness and equity are quintessentially important because all examinees should enjoy equal opportunities to perform satisfactorily on a large-scale assessment, and hence being treated equitably in terms of their test scores (Moghadam & Nasirzadeh, 2020). The distinction between item bias and item impact is defined and clarified by the purpose of the measure.…”
Section: Introductionmentioning
confidence: 99%